Investigation of the Antioxidant Effects of Amniotic Fluid on Corneal Alkali Burns - Günay, Cihan; Sağlıyan, Aydın; Yılmaz, Seval; Polat, Eren; Kaya, Emre; Han, Mehmet Cengız; Karabulut, Kenan Kemal (My University, 2020)
In the study, 40 female Wistar Albino rats were used to investigate the healing effects of amnioticfluid on corneal alkali burns. Rats were randomly divided into 4 groups of an equal numbers of rats.The groups were assigned as follows: The control group; the group “AF”, in which the rats wereapplied with bovine amniotic fluid for 20 days; the group “AB+SF”, in which an alkali burn wasformed in the right eyes of the rats and saline was applied for 20 days; and the group “AB+AF”, inwhich an alkali burn was formed in the right eyes of the rats and amniotic fluid was applied for 20days. At the end of the 20th day of the experiment, malondialdehyde (MDA) and glutathione (GSH)levels and glutathione peroxidase (GSH-Px) activity were determined in the corneal tissue of theanimals euthanized. The MDA levels and the GSH-Px activity in the corneal tissue were found tobe increased significantly in the “AB+SF” group compared to the control group. When the MDAlevels in the corneal tissue were compared between the “AB+AF” and the “AB+SF” groups, astatistically significant decrease was determined and the MDA levels approached to those obtainedin the control group. The GSH levels in the corneal tissue were lower in the “AB+SF” groupcompared to the control group; the difference between these two groups was found to besignificant. When the GSH levels in the corneal tissue were compared between the “AB+AF” andthe “AB+SF” groups, a statistically significant increase was determined and the values approachedthe control group. In conclusion, oxidative stress may play a role in corneal alkali burns, andamniotic fluid may be effective in improving it.
Keywords: Göz Hastalıkları; Biyokimya ve Moleküler Biyoloji; Veterinerlik